Stone mastic asphalt modified with nano titanium dioxide and potential exposure to blast load: A review - Nur Syafiqah Shamimi, Mohd. Zali; Khairil Azman, Masri; Mazlan, Abu Seman (Bentham Open, 2024)
This article states the modification of stone mastic asphalt with nano titanium dioxide and the advantage it has over conventional asphalt. The transport infrastructures must meet the needs of transport as well as other requirements like resilience and multi-hazard resistance in order to satisfy society's desire for sustainable development. Hence, blast load is introduced in this paper as one of the potential hazards that may be exposed to pavements. The use of SMA with nano titanium is believed to impact the pavement's behaviours significantly and can potentially resist higher blast loads and reduce failure in samples. As real field blast tests are limited, a numerical analysis is done to assess the modified pavement's enhancement. The article concludes by recommending using SMA modified with nano titanium as a promising solution to withstand blast loads in pavements.